THE EFFECT OF Plant Growth Promotong Rhizobacteria (PGPR) Mimosa pudica DOSAGE AT DIFFERENT SOIL WATER LEVELS ON THE GROWTH AND YIELD of Clitoria ternatea - Y., Ronal,; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 6 (2024): Vol. 12 No. 6 Year 2024; November - Desember, 2024)
The research aims to determine the interaction between doses of plant growth promoting rhizobacteria (PGPR) Mimosa pudica and different soil water levels on the growth and yield of Clitoria ternatea plants. This research was conducted at the Sesetan Research Station, Faculty of Animal Husbandry, Udayana University Denpasar. This research lasted for 8 weeks, using a completely randomized design (CRD) with a factorial pattern. The first factor is the PGPR dose: 0 ml pot-1 (D0); 7.5 ml pot-1 (D1); and 15 ml pot-1 (D2). The second factor is soil water content: 25% field capacity (K25), 50% field capacity (K50), and 100% field capacity (K100). There were 9 treatment combinations and each treatment had 4 replications, so there were 36 experimental units. The variables observed are growth variables, outcome variables, and growth characteristic variables. The research results showed that there was no interaction between the PGPR dose and different soil water levels for all variables. The PGPR dose of 15 ml/pot-1 (D2) gave the highest average for the variables of plant height, number of leaves and ratio of total dry weight of forage to dry weight of roots. Soil water content of 25% field capacity gave the highest average for all variables except root dry weight and the ratio of leaf dry weight to stem dry weight. From this research, it can be concluded that there was no interaction between PGPR doses and different soil water levels on the variable results of PGPR administration. Mimosa pudica showed that the results were not significantly different in all treatments, however, with a treatment dose of 15 ml pot-1, it tended to produce leaf dry weight, stem dry weight, root dry weight and total dry weight of forage were the highest compared to other treatments at a soil water content of 25% field capacity capable of increasing the growth variables of plant height, dry weight of leaves, dry weight of stems and total dry weight of of forage in Clitoria ternatea plants.